Nebivolol effect on oxidative biomarkers in Tamoxifen-Induced Hepatotoxicity in Female White Albino Rats: In Vivo Study - Noor Ahmed Hammadi; Yassir Mustafa Kamal almullahummadi; Huda Jaber Waheed (Al-Mustansiriyah Journal of Pharmaceutical Sciences)
Liver injury can arise post-exposure to drugs or their metabolites, as well as herbal and dietary supplements. Tamoxifen is a frequently used drug in breast cancer treatment. Unfortunately, Epidemiological studies have identified that Long-term tamoxifen treatment has been associated with the development of hepatotoxicity so it was used in this study to induce liver damage. Oxidative stress was the major implicated mechanism contributing to tamoxifen hepatotoxicity. Nebivolol is a third-generation selective beta1-adrenergic receptor blocker with vasodilator characteristics with significant antioxidant activity.